Impact Of Standardized Healthcare On Patient Safety And Outcomes: A Mixed-Methods (The Review of Diabetic Studies, 2025)
Standardized healthcare protocols have appeared as an important strategy for enhancing patient safety, decreasing variability in clinical practice and improving overall healthcare quality. However, their effectiveness in specialized hospitals within resource-limited frameworks stills underexplored. Aim: This study aimed to assess the effect of standardized healthcare protocols on patient healthcare outcomes in specialized hospital departments throughout quantitative post-intervention analysis.Method: A retrospective quantitative design analyzed pre- and post-accreditation data from two specialized hospitals; Al-Istishari Arab Hospital IAH (Ramallah) and Ibn Sina Specialized Hospital ISH (Jenin). A total of 1,200 inpatient medical records were reviewed, divided evenly between pre- and post-accreditation periods. Patient safety and clinical outcome indicators included infection rates (CAUTI, CLABSI), medication errors, falls, readmissions, length of stay LOS, patients’ satisfaction and staff perceptions. SPSS v24 was used for statistical analysis, performing Shapiro-Wilk tests for normality and independent samples t-tests for comparison.Results: The results showed that IAH registered improvements through most metrics, involving CAUTI (↓15%), CLABSI (↓13%), medication errors (↓17.9%) and readmissions (↓7.5%), while patient satisfaction increased by +1.1 points. ISH attained remarkable progress in medication safety (↓60%) and patient falls (↓58.5%), along with a significant reduction in LOS (from 8.60 to 4.69 days, p = 0.005). However, ISH also reported deteriorating CAUTI (+197%), CLABSI (+171%) and readmissions (+52%). Staff perceptions improved in both hospitals, although incident reporting deteriorated post-accreditation at IAH. Overall, the results enhance existing evidence that standardization improves patient outcomes, while highlighting the effect of organizational willingness, leadership involvement and resource allocation on the size and sustainability of improvements.Conclusion: Accreditation-related standardization made quantifiable gains but with hospital-specific variation. Success depended on baseline performance, implementation fidelity, and safety culture. Continuous monitoring and designed strategies are critical for sustaining improvements.